EFFECTS OF SIZE AND SAMPLING GRID ON THE QUALITY OF APPARENT SOIL ELECTRICAL CONDUCTIVITY MAPS - Oldoni, Henrique [UNESP]; Costa, Bruno R. S. [UNESP]; Rocha Junior, Romero C.; Rabe, Ladislau M.; Bassoi, Luis H. (Soc Brasil Engenharia Agricola, 2019)
The apparent soil electrical conductivity (ECa) is an attribute commonly used for the characterization of the spatial variability of soil, but its determination by handheld sensors consumes considerable time and labor. The reduction in the number of sampling points allows minimize them but can result in increased uncertainty of interpolated maps. Thus, the goal of this study was to identify the best spacing and number of ECa measurements, to guarantee the quality of maps generated in three vineyards. The ECa values were obtained using a handheld sensor in different sampling grids. The data were submitted to descriptive statistical and geostatistical analyses. The relative deviation and Kappa coefficient of agreement were used to assess the similarity of generated maps. The reduction in the number of points and increase in the size of the sampling grid reduced the quality of maps and this reduction was greater when the spacing increased in the direction of the terrain slope. A minimum limit of 100 sampling points should be considered for the sampling planning to generate ECa spatial distribution maps, with a more conservative approach when regarding the increase in spacing in the direction of the terrain slope.
Keywords: spatial variability; geostatistics; agricultural instrumentation